Stability of black sigatoka resistance in TMPx germplasm - Ortíz, R.; Vuylsteke, D.; Foure, E.; Akele, S.; Lawrence, A. (1995)
Multisite evaluation trials were performed to test the stability of yield and resistance to Black Leaf Streak (BLS) in improved Musa germplasm (TMPx for plantain hybrids and TMBx for banana hybrids). The youngest spotted leaf was used to evaluate genotype response to BLS in 20 clones (hybrids, parents and reference cultivars) in 9 environments. Regression analysis was used to describe genotype response to BLS of a given environment. The results show that selection of TMPx clones can achieve stable resistance. Resistance of hybrids bred from 'Obino l'Ewai' was generally more stable with regard to BLS than those bred from 'Bobby Tannap'.